2013
DOI: 10.1186/1742-4755-10-42
|View full text |Cite
|
Sign up to set email alerts
|

Odon device: a promising tool to facilitate vaginal delivery and increase access to emergency care

Abstract: The last innovation in operative vaginal delivery happened centuries ago with the invention of the forceps and the vacuum extractor. The World Health Organization Odon Device Research Group recently published a protocol for a feasibility and safety study for a new device (Odon device) which aims to revolutionize assisted vaginal delivery. This editorial discusses the device and its pathway to global use. Although preliminary results look promising, the rigorous three-phased WHO protocol needs completion before… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…14 Of note, the WHO is currently testing a new device called the Odon device as an alternative method to vacuum and forceps for assisted vaginal delivery, suggesting that the organization does value OVD as an alternative to CD and is researching and promoting its use. 15…”
Section: Discussionmentioning
confidence: 99%
“…14 Of note, the WHO is currently testing a new device called the Odon device as an alternative method to vacuum and forceps for assisted vaginal delivery, suggesting that the organization does value OVD as an alternative to CD and is researching and promoting its use. 15…”
Section: Discussionmentioning
confidence: 99%
“…The Odon device may be easier and safer to apply than forceps or the vacuum extractor [ 47 ]. It could play a signifi cant role in low-resource settings that lack surgical capacity or personnel trained in the use of a vacuum extractor or forceps delivery [ 48 ]. Early simulation trials showed that the Odon device consistently facilitates immediate expulsion of the fetus [ 47 ].…”
Section: Innovations That Address Obstructed Labormentioning
confidence: 99%
“… 2 An innovative device that is easier and safer to use could increase women’s access to AVB, which in turn would help to reduce the number of emergency caesarean sections performed in the second stage. 3 4 …”
Section: Introductionmentioning
confidence: 99%